Pelatihan Pembuatan Detergen Cair Berbasis Determat: Solusi Hemat Untuk Ibu Rumah Tangga di Desa Waylunik Kabupaten Lampung Utara - Rahmawati Azizah; Syara Purnama Sari; Ria Octavia; Asri Winanti Madyoningrum (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The Community Service Program of STIE Al-Madani in Waylunik Village, North Lampung, focused on improving household economic skills through Determat-Based Liquid Detergent Making Training for 20 housewives. This training is intended to overcome long-term problems and meet basic household needs while creating independent business opportunities. The method used is a demonstration followed by the practice of making liquid detergent and an interactive discussion of the effectiveness and safety of Determat-based materials. Participant evaluation was carried out through observation and questionnaires to measure the understanding gained and the potential for application in everyday life. The results of the activity showed that all participants were able to mix liquid detergent using easily accessible and economical ingredients. Post-training assistance through online discussion forums is expected to encourage the sustainability of the program and encourage the development of community-based business models. Thus, this activity not only contributes to household economic empowerment but also educates and fosters innovation in managing household food needs.